2021
DOI: 10.1007/s10639-021-10819-2
|View full text |Cite
|
Sign up to set email alerts
|

Learning from text and video blogs: comprehension effects on secondary school students

Abstract: Informational video blogs are a popular method of communication among students that may be fruitful educational tools, but their potential benefits and risks remain unclear. Streaming videos created by YouTubers are often consumed for entertainment, which may lead students to develop habits that hinder in-depth information processing. We aimed to test this hypothesis by comparing students’ perceived attention to task, metacognitive calibration of their level of comprehension, and comprehension outcomes between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 52 publications
2
8
0
3
Order By: Relevance
“…Thus, they would apply more efficient regulation strategies to better align the actual difficulty of the information conveyed in videos with the time devoted to studying them. This interpretation and the results of List (2018) would agree with the results of a subsequent study conducted by the research team of Salmer on (Delgado et al, 2021) which revealed that the effect of blog format (video or text) was not significant regarding comprehension accuracy for secondary students (9th and 10th grade).…”
Section: Learning From Online Blog Posts: Text Versus Videosupporting
confidence: 89%
See 2 more Smart Citations
“…Thus, they would apply more efficient regulation strategies to better align the actual difficulty of the information conveyed in videos with the time devoted to studying them. This interpretation and the results of List (2018) would agree with the results of a subsequent study conducted by the research team of Salmer on (Delgado et al, 2021) which revealed that the effect of blog format (video or text) was not significant regarding comprehension accuracy for secondary students (9th and 10th grade).…”
Section: Learning From Online Blog Posts: Text Versus Videosupporting
confidence: 89%
“…Regarding the influence of blog format on comprehension accuracy, we could say that, in light of our results, young adults with intellectual disability benefit equally from learning through text-blog posts and video-blog posts. This result contrasts with the negative effect of video on learning reported by Salmer on et al ( 2020) in children, but they are in line with the absence of a media effect on comprehension reported by List (2018) with undergraduates and by Delgado et al (2021) with secondary students. Thus, we can elucubrate that older students with intellectual disability probably have enough experience with watching videos for learning, which would allow them to develop efficient regulation strategies, as in text reading.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Many of these videos are focused on educational content that pertains to different disciplines. As noted by Delgado et al (2021), educational video blogs (vblogs) are very popular among young people and constitute a large share of the YouTube videos. Among the characteristics of such videos is interactivity, that is, viewers can pause, re-watch some parts, or advance fast.…”
Section: Integrated Understanding Of Complementary Texts and Videosmentioning
confidence: 99%
“…This makes videos comparable to texts where readers can re-read sentences and paragraphs as well as skip parts of the text. The interactivity of the learning material is a relevant characteristic for learning (Delgado et al, 2021); in fact, studies comparing digital texts and interactive videos have shown no medium difference with respect to comprehension (e.g., Burin et al, 2021;Delgado et al, 2021;Salmerón et al, 2020;Tarchi, 2021). For example, no effect of medium on comprehension performance emerged in a recent study that compared digital text, video in the form of audio explanation with written keywords, and video that also added dynamic decorative and irrelevant images as seductive details to the previous type (Burin et al, 2021).…”
Section: Integrated Understanding Of Complementary Texts and Videosmentioning
confidence: 99%